PENGARUH INOVASI TERHADAP KINERJA PEMASARAN UMKM DI KOTA PALU - Nurfitriani (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
In business operations, performance marketing is very useful. The innovations carried out by MSME implementers also have an impact on the ongoing marketing strategy. The purpose of this research is to identify how innovation affects the marketing performance of MSMEs in Palu. In order to determine how innovation affects the marketing performance of MSMEs in the city of Palu, so that the research design is of high quality in this research. This research uses clause procedures and is quantitative in nature. 70 people who completed UMKM in the city of Palu became a research illustration. The sample used was purposive sampling, a non-probability sampling procedure, used to sort out the sample. On the other hand, validity and reliability tests are used to test the instrument. Simple regression, t test, correlation test, and determination test are the information analysis methods used. According to research findings and subsequent reviews, it can be said that innovation has a positive influence on the marketing performance of MSMEs in Palu. The result of t count is greater than t table 2, 040 > 1, 667 supports this matter. This finding shows how valuable innovation is to increase the marketing efficiency of MSMEs in Palu City.